2013
DOI: 10.1007/s12639-013-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the gill tissues of goldfishes (Carassius auratus) parasitized by Dactylogyrus spp

Abstract: The aim of this study was to investigate the status of oxidative stress in the gill tissues of goldfishes (Carassius auratus) parasitized by Dactylogyrus spp. We therefore compared the concentrations of malondialdehyde (MDA) and total thiol groups in the gill tissues of parasitized and non-parasitized goldfishes. 15 goldfishes parasitized by Dactylogyrus spp. along with 15 nonparasitized goldfishes were selected for the study. A significant increase in MDA concentration (P \ 0.01) and a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…SOD and GSH‐Px are considered as antioxidants, which counteract oxidative stress caused by the ROS in fish (Jiang et al, ; Martínez‐Álvarez, Morales, & Sanz, ). MDA is used as a biomarker of oxidative damage since it is a product of lipid peroxidation (Mozhdeganloo & Heidarpour, ). Our results indicated that supplementation of BG in diet could enhance fish's antioxidant activity and alleviate oxidative damage caused by the ANF in high SBM‐based diets.…”
Section: Discussionmentioning
confidence: 99%
“…SOD and GSH‐Px are considered as antioxidants, which counteract oxidative stress caused by the ROS in fish (Jiang et al, ; Martínez‐Álvarez, Morales, & Sanz, ). MDA is used as a biomarker of oxidative damage since it is a product of lipid peroxidation (Mozhdeganloo & Heidarpour, ). Our results indicated that supplementation of BG in diet could enhance fish's antioxidant activity and alleviate oxidative damage caused by the ANF in high SBM‐based diets.…”
Section: Discussionmentioning
confidence: 99%
“…The host response is characterized by enhanced synthesis of reactive oxygen species aimed at parasite elimination. This process can both inhibit and stimulate antioxidant enzyme activities (Bello et al, 2000;Mukjrakov & Silkina, 2006;Skuratovskaya et al, 2013Skuratovskaya et al, , 2015Skuratovskaya et al, , 2019Mozhdeganloo & Heidarpour, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Host responses to parasites are varied and manifest at different levels, including immunological reactions, physiological and biochemical changes in their metabolism. Infections cause biochemical rearrangements in the infected host tissues and can bring about serious structural and functional changes in the infected organs (Mukjrakov & Silkina, 2006;Skuratovskaya et al, 2013Skuratovskaya et al, , 2015Skuratovskaya et al, , 2019Eissa et al 2014;Mozhdeganloo & Heidarpour, 2014;Jang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under some oxidative/nitrosative stress conditions, such as those attributed to intensive fish culture practices, dietary supplementation with exogenous antioxidants such as vitamins, flavonoids, carotenoids, plant polyphenols, allyl sulfides, curcumin, melatonin, or polyamines may offer a good functional strategy to maintain proper levels of RONS (23,25,26). Although most of the studies investigating fish oxidative stress are related to the effects of xenobiotics or pollutants, the use of functional additives, which are capable of triggering the fish antioxidant system, has gained attention during the last decade in aquaculture because of its potential benefit in preventing diseases and promoting health (17,(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%